Pathological Role of Peptidyl-Prolyl Isomerase Pin1 in the Disruption of Synaptic Plasticity in Alzheimer’s Disease - Lingyan Xu; Zhiyun Ren; Frances E. Chow; Richard Tsai; Tongzheng Liu; Flavio Rizzolio; Silvia Boffo; Yungen Xu; Shaohui Huang; Carol F. Lippa; Yuesong Gong (Neural Plasticity)
Synaptic loss is the structural basis for memory impairment in Alzheimer’s disease (AD). While the underlying pathological mechanism remains elusive, it is known that misfolded proteins accumulate as β-amyloid (Aβ) plaques and hyperphosphorylated Tau tangles decades before the onset of clinical disease. The loss of Pin1 facilitates the formation of these misfolded proteins in AD. Pin1 protein controls cell-cycle progression and determines the fate of proteins by the ubiquitin proteasome system. The activity of the ubiquitin proteasome system directly affects the functional and structural plasticity of the synapse. We localized Pin1 to dendritic rafts and postsynaptic density (PSD) and found the pathological loss of Pin1 within the synapses of AD brain cortical tissues. The loss of Pin1 activity may alter the ubiquitin-regulated modification of PSD proteins and decrease levels of Shank protein, resulting in aberrant synaptic structure. The loss of Pin1 activity, induced by oxidative stress, may also render neurons more susceptible to the toxicity of oligomers of Aβ and to excitation, thereby inhibiting NMDA receptor-mediated synaptic plasticity and exacerbating NMDA receptor-mediated synaptic degeneration. These results suggest that loss of Pin1 activity could lead to the loss of synaptic plasticity in the development of AD.